Understanding reference transactions transforming an art into a science - Richardson, John V., 1949- (Academic Press, 2002)
The goal of this book is to improve reference service in libraries and information centers, by improving the accuracy of answering capabilities. The authors provide a detailed analysis of the question-answering process and methods of evaluating the completeness, usefulness, user satisfaction, and accuracy of the information provided. This is an important contribution to library studies, and it will be a useful textbook for teaching references courses in library schools. Powerful research models help explain what is happening in the reference transaction. It encompasses a comprehensive review of the research literature. It offers a unique systems analysis of the reference transaction and includes a detailed appendix of the concepts, operational definitions, and research variables used to measure outcomes as well as statistical results from all known prior studies.
Keywords: Reference services (Libraries); Interviewing.; elektronické knihy; electronic books